On the estimation of error in measuring the residual stress by strain gauge rosette. (April 2015) - Giri, A.; Pandey, C.; Mahapatra, M.M.; Sharma, K.; Singh, P.K.
Highlights: Plasticity and stress concentration effects on blind hole drilling were investigated. Strain gauge rosettes with different hole diameters were blind hole drilled. Uniaxial calibration test of rosettes were conducted with control gauges. Effect of biaxial state of stresses on the rosettes were investigated through FEM. Correlations were developed to calculate correct value of residual stress. Abstract: The blind hole drilling technique, utilized for measuring residual stress by using strain gauge rosette, is associated with plastic deformation of material that is removed from the hole and also with stress concentration effect of multi point cutting tool. Further, the plasticity effect is also induced in presence of high applied stress which may lead to local yielding of the hole boundary. The present paper describes the plasticity and stress concentration effects of blind hole drilling technique on the calculation of residual stresses for SS 304L and modified Cr–Mo Grade 91 alloys. For uniaxial loading, the responses of strain gauge rosettes were investigated experimentally through tensile testing and for biaxial loading through numerical modeling. Correlations were developed to directly calculate the corrected values of residual stresses from the experimental strain data obtained through the strain gauge rosette and from stress values as per ASTM E837-13.